(untitled) (Res Gesta, 2018)
Social and cultural dynamics of adoptive families are aspects of the adoption phenomenon that have not yet met a specific analysis in Argentina. In these pages, we try to advance on that, reconstructing family configuration and the experiences of the child arrival to the home of those who turned to juvenile courts in Córdoba between 1957 and 1974 to request custodies with the aim of adopting, from the analysis of court files that resorts to other sources and to quantification operations, reducing the scale of observation and contextualization. Thought as a contribution to the deliberations over the relationships between family and State, the investigation shows that social and cultural inscription of adoptive families, during the sixties, was related to a decentralized configuration in the delivery of children, nourished by institutional discretions and families that turned judicial branch into a scenario of validations and negotiations of practices and guidelines of family life.